(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted for two consecutive winterseasons (2004/05 and 2005/2006) at Shambat Research Farm, KhartoumState (Sudan) to study the performance of three winter sown forage cerealcultivars at five sowing dates. The objective of the study was to enable thefarmers to choose the most suitable forage crop for each sowing date inKhartoum State. The treatments comprised three cultivars, viz. a localvariety of barley (Hordeum vulgare), referred to as ‘Baladi’, a localvariety of maize (Zea mays) referred to as ‘Higeri’ and sorghum(Sorghum bicolor) cultivar ‘Abu Sabeen’, sown at five sowing dates viz. 1and 15 December, 1 and 15 January and 1 February in each season. Asplit-plot design with three replicates was used to execute the experiment.The sowing dates were assigned to the main plots and the cultivars to thesubplots. At harvest, data were collected on the number of culms/m 2 ,number of days to harvest, plant height and the forage dry matter yield.The results indicated that the dry matter yields of barley were the highestin each of the first three sowing dates, whereas those of sorghum were thehighest in the last two sowing dates. The dry matter yield of maize wascomparable to that of sorghum during the first three sowing dates but wasmarkedly lower during the last two sowing dates. Hence, 15 of Januarycould be considered as a critical sowing date for the crop choice betweenbarley and sorghum in Khartoum State.